DISCOVERING SEMANTIC CHANGES IN SELECTED NEWS ARTICLES FROM THE JAKARTA POST (Sastra Inggris UNPAM, 2022)
This study aims to identify the types and factors of semantic changes in The Jakarta Post articles. The Jakarta Post is the name of the Indonesian English-language national newspaper headquartered in Jakarta. The Jakarta Post newspaper is published by PT Bina Media Tenggara. This study uses a qualitative descriptive method using two theories, namely the theory of Leonard Bloomfield (1933), to find the type of change in meaning and the theory of Stephen Ullman (1983) to dissect the factors causing the change in meaning. The result showed that there are seven types of meaning changes contained in 34 words in the selected articles of The Jakarta Post. The seven types of meaning change include meaning expansion, meaning narrowing, metaphor, litotes, metonymy, hyperbole, and pejorative. Furthermore, some of the factors contained in the selected news articles are the linguistic cause, psychological cause, need for a new name, social cause, existence of polysemy, metaphorical cause, the taboo of propriety, historical cause, structure of vocabulary, and loss of motivation. Keywords : factors of semantic changes, semantic changes, the Jakarta Post article, types of semantic changes